2016
DOI: 10.21273/horttech.26.4.379
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose Application of Nonionic Alkyl Terminated Block Copolymer Surfactant Enhances Turfgrass Seed Germination and Plant Growth

Abstract: Rapid seed germination and vigorous seedling growth are desired when establishing turfgrass lawns from seed. Low-dose concentrations of nonionic, block copolymer surfactants can have a direct effect on plant physiological functions and growth. The objectives were to determine if a low-dose application of a nonionic alkyl ended block copolymer surfactant applied directly to the seed, within a film coating, would 1) influence speed, synchrony, and final germination percentage (FGP), and 2) enhance seedli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Overall, grazing treatments had a much weaker negative effect on seedling densities in subplots planted with coated seeds. The surfactant coating that was applied to the seeds has been shown in previous studies to improve seedling survival under drought stress (Ahmed et al, ; Madsen et al, ; Madsen, Kostka, et al, ). We hypothesize that in this dryland study the soil surfactant in the coating helped produce more robust plants that were able to recover quicker after the grazing treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, grazing treatments had a much weaker negative effect on seedling densities in subplots planted with coated seeds. The surfactant coating that was applied to the seeds has been shown in previous studies to improve seedling survival under drought stress (Ahmed et al, ; Madsen et al, ; Madsen, Kostka, et al, ). We hypothesize that in this dryland study the soil surfactant in the coating helped produce more robust plants that were able to recover quicker after the grazing treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, grazing treatments had a much weaker negative effect on seedling densities in subplots planted with coated seeds. The surfactant coating that was applied to the seeds has been shown in previous studies to improve seedling survival under drought stress (Ahmed et al, 2018;Madsen et al, 2012Madsen et al, , 2014Madsen, Kostka, et al, 2016).…”
Section: Strategic Restoration To Mitigate Tradeoffsmentioning
confidence: 99%
“…Seed coating and pelleting refers to the process whereby materials are applied to the surface of the seed to improve their seed sowing attributes and seed performance. These materials vary with the intended function, and they include coats designed to decrease water repellence (Madsen et al 2013), protect the seed from predators (Taylor et al 2020), and provide protection from soil pathogens (Hoose et al 2022). Studies which involve arid environments or related species have found success using specific types of coat, such as fungicide coats (Hoose et al 2022), germination delaying coats (Madsen et al 2016), herbicide protection coats made of activated carbon (Brown et al 2023; Munro et al 2023), and water‐ absorbing coats (Madsen et al 2013).…”
Section: Revegetation Methods Available For Use In the Arid Zone And ...mentioning
confidence: 99%
“…Nutrient amendments in coatings mainly focus on the delivery of polymer micronutrients, for example, copper, manganese, and zinc [ 36 ], which are used to compensate for soil deficiencies in these trace elements. The combination of growth stimulants properties and their application through seed coating has the pronounced potential for enhancing plant performance [ 63 ]. There are various categories of growth stimulants, such as plant-derived proteins [ 43 , 64 ], protein hydrolysates and amino acids [ 50 , 76 ], carbohydrate derivatives [ 59 ], and herbal extracts [ 77 ].…”
Section: Seed Coating Agentsmentioning
confidence: 99%